Experiences and coping strategies of adolescents living with Type 1 Diabetes Mellitus: A Descriptive phenomenological study - Sipho Fakudze; Mamba, Welile (KHD-Production, 2025)
Adolescents with type 1 diabetes mellitus fail to achieve glycemic control typically because of poor performance in administering insulin injections, monitoring blood glucose, adhering to meal plans, and engaging in appropriate exercises. Little is known about the lived experiences and coping strategies of adolescents living with type 1 diabetes mellitus. The study aimed to explore the lived experiences and coping strategies of adolescents living with type 1 diabetes mellitus in the Hhohho region of Eswatini. A qualitative, descriptive, phenomenological design was used. Data were collected through in-depth individual telephone interviews using a semi-structured interview guide from a purposively selected sample. Data were analyzed using thematic analysis guided by Braun and Clarke’s approach. Findings revealed that participants experienced mental health challenges, alterations in their social life, especially relationships with peers, and restrictions in terms of diets, glycemic control, and physical limitations. Coping mechanisms reported by participants included adherence to prescribed diets, use of technology in assistive devices, and engagement in physical activity. Adolescents living with type 1 diabetes mellitus need close monitoring by both healthcare professionals and their caregivers to achieve reasonable glycemic control. Additionally, focused psychosocial interventions are needed to enhance resilience among adolescents with type 1 diabetes mellitus and help them cope with the demands of and stress associated with having the disease. Future research should investigate factors associated with the negative experiences of adolescents living with diabetes mellitus.